Let us first write (6i-4) and (-3i-5) in trigonometric form.
a+ib can be written in trigonometric form re^(itheta)=rcostheta+irsintheta=r(costheta+isintheta),
where r=sqrt(a^2+b^2) and tantheta=b/a or theta=arctan(b/a)
Hence 6i-4=(-4+6i)=sqrt((-4)^2+6^2)[cosalpha+isinalpha] or
sqrt52e^(ialpha), where tanalpha=6/(-4)=-3/2 and
-3i-5=(-5-3i)=sqrt((-5)^2+(-3)^2)[cosbeta+isinbeta] or
sqrt34e^(ibeta], where tanbeta=(-3)/(-5)=3/5
Hence (6i-4)/(-3i-5)=(sqrt52e^(ialpha))/(sqrt34e^(ibeta])=sqrt(26/17)e^(i(alpha-beta))=sqrt(28/17)(cos(alpha-beta)+isin(alpha-beta))
Now, tan(alpha-beta)=(tanalpha-tanbeta)/(1+tanalphatanbeta)
= (-3/2-3/5)/(1+(-3/2)*(3/5))=(-21/10)/(1-9/10)=-21/10*10/1=-21
Hence (6i-4)/(-3i-5)=sqrt(26/17)(cosrho+isinrho) where rho=tan^(-1)21